DETEKTOR FINANCIAL DISTRESS PERUSAHAAN PERBANKAN INDONESIA - Kun Ismawati; Paula Chrisna Istria (JURNAL EKONOMI BISNIS DAN KEWIRAUSAHAAN, 2015)
This research aims to determine the effect of the CAMEL ratio in detecting financial distress in banking companies in Indonesia. The CAMEL ratio consists of CAR(Capital Adequacy Ratio), ROE (Return On Equity), ROA (Return On Assets), NPL (Non Performing Loan), LDR (Loan To Deposit Ratio), and BOPO (operational expense tooperational income). Purposive sampling method used in this research. The number of samples obtained were 31 banking companies, divided in two categories: 25 banks with â€œno problemâ€and 6 banks â€œin troubleâ€. Research samples in the form of secondary data, which listed in the Indonesia Stock Exchange during the period 2010-2013. The statistical method used to test the hypothesis of the research is logistic regression. Results of the analysis indicate that CAR and BOPO variables have positive but not significant effect; ROE variables have negative and not significant effect; ROA variables have negative and not significant effect; NPL and LDR variables have positive and significantly effect the probability of financial distress in banking companies in Indonesia. Logistic regression estimation shows the ability to detect from six independent variables on the probability of financial distress in the banking company by 80,4%, while the remainder explained by other variables outside the model